Ethical Dimensions in Global Climate Change Exploring a Philosophical Perspective: An Analytic Approach - Muthusamy Murugan2, S.K. Arun Murthi1 and (Recent Research in Science and Technology, 2011)
Climate change poses a global challenge that calls for solution and urgent actions that need to be formulated in policy making. These issues are loaded with ethical implications which arise in policy debates. This paper tries to analyze the ethical issues of climate change within the framework of analytic ethics of the western philosophical tradition. This paper attempts to bring metaethics and principles of normative ethics within the present context of climate change and thus provide a philosophical foundation to the ethical problems relevant to policy debates. We have proposed that the ethics of global climate change be considered a subdivision of applied ethics.